Susan Weingarten: Haroset: A Taste of Jewish History - Mills, Matilda (Petits Propos Culinaires, 2021)
Susan Weingarten: Haroset: A Taste of Jewish History: Toby Press, 2019: 192 pp., hardback, £18.99.